Association of Epithelial Cell Abnormality in Pap Smear Cytology with Histopathology - Baral, Alina; Goyal, Binita; Pun, Chin Bahadur (Journal of College of Medical Sciences-Nepal, 2025)
Background Cervical cancer is the fourth most common cancer among female globally while in Nepal it is the second most common cancer among female. Papanicolaou (PAP) test is a cytological screening technique which is simple, non- invasive and effective method for detection of pre-cancerous and non- cancerous lesions in cervix. The pre invasive phase of cervical carcinoma has a long course thus early identification in its precursor state is beneficial. This study aims to study association between pap smear cytology and histopathology in the cases reported as epithelial cell abnormality in cytology. Methods Cross sectional study was conducted over the period of 5 years at Department of Pathology, COMS-TH, Nepal. Cases with both pap smear cytology and its corresponding histopathology diagnosis were included in the study. Study of association between cytology and histopathology was done. Results Total of 82 cases of epithelial abnormalities on cytology were included with corresponding histopathology. ASCUS was the commonest abnormality reported accounting for 48.8% of cases. ASCUS, LSIL,ASC-H, HSIL and SCC had concordance of 77.5%, 62.5%, 46.15%, 40%, 100% respectively with histopathology. The association of epithelial abnormalities in Pap smear cytology with histopathology was statistically significant with p-value of <0.001. Conclusions Pap smear is cost-effective, easily available method of cervical cancer screening. It has excellent correlation with histopathological diagnosis. Thus, cervical cancer screening program should be conducted widely to decrease the cancer burden. Furthermore, cases of ASCUS or ASCH should be followed up by biopsy and adjunctive tests whenever necessary.